Otimização de estruturas treliçadas considerando análise não linear e carregamento dinâmico - Domingues, Bárbara Scardini (2024)
Structural optimization techniques help designers to develop economical projects more efficiently, in addition to automating the design process. Some large-scale truss structures may present dynamic loading, large displacements, and material plastification, requiring a nonlinear analysis. Therefore, this work aims to optimize truss structures considering geometric and material nonlinear behavior when subjected to dynamic loading. Thus, it was necessary to determine the cross-sectional area of the bars that minimizes the total mass of the structure, imposing constraints on nodal displacements, axial stresses, and axial compression force. For the optimization problem, a computational program was developed on the Matlab platform using Particle Swarm Optimization (PSO) and the Genetic Algorithm (GA), a native Matlab tool to verify the results. The geometric and material nonlinear dynamic analysis procedure was performed using the Ansys software, with the Newmark method coupled with the Newton-Raphson method. Examples of plane and spatial trusses subjected to different types of dynamic loading were solved using the developed computational program and validated by comparison with solutions present in the literature. The results indicated that the effect of nonlinearities on the optimized structures is particular to each case, PSO was the algorithm that shown best performance and robustness and the damping effect led to a reduction in the final mass